Business in Social Work Education: A Historically Black University’s Social Work Entrepreneurship Project. - Archibald, Paul; Muhammad, Omar; Estreet, Anthony (Journal of Social Work Education)
The destabilization of the current economy has sparked increased interest in entrepreneurship, especially for underrepresented minority social work students. The entrepreneurial thinking of these social work students entering social work programs at historically Black colleges and universities needs to be fostered in a learning environment. This article describes a historically Black university’s creative social entrepreneurship venture in response to the Social Work Congress’s 2010 imperative “Business of Social Work—Infuse models of sustainable business and management practice in social work education and practice.” The social entrepreneurship project uses the interprofessional collaborative educational model and attempts to provide meaningful and relevant education to social work students interested in social entrepreneurship through the collaborative efforts of the university’s School of Social Work and the School of Business and Management.